Increase of Reproductive Life Span Delays Age of Onset of Parkinson’s Disease - Frentzel, Dominik; Judanin, Grigorij; Borozdina, Olga; Klucken, Jochen; Winkler, Jürgen; Schlachetzki, Johannes C. M. (Frontiers in Neurology, 2017)
One striking observation in Parkinson’s disease is the remarkable gender difference in incidence and prevalence of the disease. Data on gender differences in regard of disease onset, motor and non-motor symptoms as well as dopaminergic medication is limited. Furthermore, whether estrogen status affects disease onset and progression in Parkinson’s disease is controversially discussed. In this retrospective single-center study we extracted clinical data of 226 ambulatory PD patients and compared age of disease onset, disease stage, motor impairment, non-motor symptoms, and dopaminergic medication between genders. We applied a matched-pairs design to adjust for age and disease duration. To determine the effect of estrogen-related reproductive factors including number of children, age at menarche and menopause on age of onset, we applied a standardized questionnaire and performed a regression analysis. The male to female ratio in the present Parkinson’s disease cohort was 1.9 to 1 (147 men vs. 79 women). Male patients showed increased motor impairment compared to female patients. The levodopa equivalent daily dose of male patients was increased by 18.9% compared to females. Matched-pairs analysis confirmed the increased dose of dopaminergic medication in male patients. No differences were observed in age of onset, type of medication, and non-motor symptoms between both groups. Female reproductive factors including number of children, age at menarche, and menopause were positively associated with a delay of disease onset up to 30 months. The disease-modifying role of estrogen related outcome measures warrants further clinical and experimental studies targeting gender differences, specifically hormone dependent pathways in Parkinson’s disease.